LIE-ADMISSIBLE HYPERALGEBRAS - Santilli, R.M.; Vougiouklis, T. (Italian Journal of Pure and Applied Mathematics, 2013)
We review Albert's axioms of Lie-admissible algebras, Santilli's geno- and hyper- mathematics with a Lie-admissible structure, and Vougiouklis Hv-hyperstructures; we then introduce Lie-admissible hyperstructures; and point out their expected relevance for biological structures and other fields.